Tailoring Rydberg interactions via Förster resonances: state combinations, hopping and angular dependence. (22nd July 2016) - Paris-Mandoki, Asaf; Gorniaczyk, Hannes; Tresp, Christoph; Mirgorodskiy, Ivan; Hofferberth, Sebastian
Abstract: Förster resonances provide a highly flexible tool to tune both the strength and the angular shape of interactions between two Rydberg atoms. We give a detailed explanation about how Förster resonances can be found by searching through a large range of possible quantum number combinations. We apply our search method to SS, SD and DD pair states of 87 Rb with principal quantum numbers from 30 to 100, taking into account the fine structure splitting of the Rydberg states. We find various strong resonances between atoms with a large difference in principal quantum numbers. We quantify the strength of these resonances by introducing a figure of merit C ˜ 3 which is independent of the magnetic quantum numbers and geometry to classify the resonances by interaction strength. We further predict to what extent excitation exchange is possible on different resonances and point out limitations of the coherent hopping process. Finally, we discuss the angular dependence of the dipole–dipole interaction and its tunability near resonances.